Family Communication Patterns and Adolescent Sexual and Reproductive Health: Experiences from Coastal Communities in Ghana - Adzovie, Rita Holm; Adzovie, Daniel Edem (Technium Social Sciences Journal, 2020)
A good understanding of human growth and development helps in the smooth transition of an individual from one stage to another. One of such stages is adolescence, which presents a lot of challenges as well as opportunities. There are differences in the extent to which families encourage conversation, the extent to which they demand conformity to family values as well as the extent to which families pass down strongly held family values from one generation to another, regarding changes that occur during adolescence. The study examines Parent-Child Communication Patterns between parents and adolescents in coastal communities in Ghana. Also, the study explored the effects of parent-child communication related to sexual and reproductive health in improving adolescent sexual reproductive health practices in Ghana. Data was collected from 300 adolescents in selected coastal communities within the Cape Coast Metropolis in Ghana. We found that many parents in the coastal communities within the Cape Coast Metropolis are unable to transmit SRH information to their children. The findings also revealed that level of formal education influenced parents’ ability to transmit SRH information to adolescents and exposes poor parent-adolescent relationship regarding SRH information in the communities studied. Aside from contributing to literature and informing policy directions on family communication patterns regarding adolescent SRH, the study brings more insight on how parents and their adolescents along coastal communities in Cape Coast, Ghana communicate SRH issues. Implications for counselling are outlined.